Impact of living and working in the heat on cognitive and psycho-physiological responses in outdoor fly-in fly-out tradesmen: a mining industry study - Taggart, Sarah M.; Girard, Olivier; Landers, Grant J.; Ecker, Ullrich K. H.; Wallman, Karen E. (Frontiers in Physiology, 2023)
Objective: This study aimed to evaluate complex cognitive function, manual dexterity and psycho-physiological parameters in tradesmen working outdoors in the mining industry during summer and winter. Methods: Twenty-six males working in a mining village in the north-west of Australia were assessed pre- and post- an 11-h shift at the start, middle, and end of a 14-day swing in summer (average daily temperature: 33.9˚C, 38% RH; n=12) and winter (24.3˚C, 36% RH; n=14). Results: Working memory performance did not differ between seasons, over the swing or shift (p≥0.053). Processing efficiency and manual dexterity performance did not differ between seasons (p>0.243), yet improved over the course of the swing (p<0.001) and shift (p<0.001). Core temperature, heart rate, thermal comfort, rating of perceived exertion and thermal sensation were not significantly different between seasons (p>0.076); however, average shift dehydration was greater in winter compared to summer (1.021±0.005 vs. 1.018±0.006; p=0.014). Conclusion: The ability to self-regulate the intensity of activity likely helped outdoor workers to thermoregulate effectively, minimising thermal strain during their swings and shifts, in turn explaining unaltered cognitive function and manual dexterity performance between seasons. Regardless of season, workers should receive education on dehydration and workplace risks to protect their health.